Brand Management, Competitiveness and Business Performance in Mexican Small Service Businesses - Maldonado-Guzman, Gonzalo; Pinzon-Castro, Sandra Yesenia; Rodriguez-Gonzalez, Ruben Michael (International Journal of Asian Social Science, 2018)
Brand management is considered in the current marketing literature as one of the most important business strategies, not only by researchers and academics but also by professionals in the field of marketing, which can allow the growth in the level of competitiveness of small service enterprises, as well as have a significant increase in their level of business performance. Moreover, brand management has usually focused on big transnational enterprises and there are relatively few investigations that have focused on small firms. There are even less research papers that have made emphasis in small service businesses. Therefore, with a sample of 150 small service businesses, the aim of this empirical research is the analysis and discussion of brand management at the level of competitiveness and business performance in small service businesses in a country with an emerging economy, which is the case of Mexico. The results obtained show that brand management has positive, significant effects in the level of competitiveness and the level of business performance.